2021
DOI: 10.1002/mame.202100159
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cellulose Reinforced Polyaniline Electroconductive Hydrogel with Multiple Weak H‐Bonds as Flexible and Sensitive Strain Sensor

Abstract: Hydrogel, as a promising soft material, possesses many functional advantages such as stretchability, viscoelasticity, and biocompatibility. An advanced electronic platform for strain sensor is constructed by modifying hydrogels with various doping techniques. Herein, a novel flexible conductive hydrogel is synthesized by combination of bacterial cellulose/sodium alginate/polyacrylamide with the polyaniline (BSP‐PANI) through multiple intermolecular interactions. In the obtained BSP‐PANI hydrogel system, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 57 publications
(63 reference statements)
2
13
0
Order By: Relevance
“…When the strain was 550%, the GF was 3.1, which was superior to many reported sensors. [10,[42][43][44][45] In addition, ΔR/R 0 under different strains (10%, 20%, 50%, and 100%) was also measured, as shown in Figure 6b, the PCT hydrogels displayed reproducible and reliable responses in the five cycles which was also consistent with the calculated parabolic equation. Figure 6c illustrated the ΔR/R 0 signal and strain versus time, indicating that there was no obvious delay in signal transmitting.…”
Section: Pct Hydrogels As Wearable Strain Sensorssupporting
confidence: 67%
“…When the strain was 550%, the GF was 3.1, which was superior to many reported sensors. [10,[42][43][44][45] In addition, ΔR/R 0 under different strains (10%, 20%, 50%, and 100%) was also measured, as shown in Figure 6b, the PCT hydrogels displayed reproducible and reliable responses in the five cycles which was also consistent with the calculated parabolic equation. Figure 6c illustrated the ΔR/R 0 signal and strain versus time, indicating that there was no obvious delay in signal transmitting.…”
Section: Pct Hydrogels As Wearable Strain Sensorssupporting
confidence: 67%
“…3d shows the performance comparison between this work and previous studies. [40][41][42][43][44][45] As shown in Fig. 3b, the DR/R 0 value of the hydrogel sensor increases significantly with the increasing tensile strain and decreases immediately after release, providing a fast response (0.75 s) and recovery (0.81 s) performance.…”
Section: Pam/sa/mxene Hydrogel-based Strain Sensorsmentioning
confidence: 88%
“…However, it has been reported that BC tends to form hydrogen bonds with other polymeric structures bearing hydrogen bonding groups, including EVOH. 43,44 It is assumed that the contribution of hydrogen bonds between EVOH and BC is relatively large under the condition of a high IPA ratio. When the ratio of the more polar solvent (water) is increased, it is expected that the hydrogen bonds between BC and EVOH decrease as it interferes with the formation of such bonds.…”
Section: Materials Advancesmentioning
confidence: 99%